1998
DOI: 10.1093/oxfordjournals.jbchem.a021962
|View full text |Cite
|
Sign up to set email alerts
|

Further Characterization of Equine Brain Gangliosides: The Presence of GM3 Having N-Glycolyl Neuraminic Acid in the Central Nervous System

Abstract: Equine brain gangliosides were isolated and their structures were characterized, to examine whether equine brain has N-glycolyl neuraminic acid in gangliosides, since other mammals predominantly possess N-acetyl neuraminic acid in brain gangliosides, and equine erythrocytes and organs except the brain have gangliosides exclusively containing N-glycolyl neuraminic acid. The gangliosides purified from the brain were identified by proton NMR spectroscopy and mass spectrometry, as well as GLC, resulting in their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Relative Absence of Neu5Gc Is a Conserved Feature of Vertebrate Brain-Prior studies of sialic acids in the vertebrate brain have either failed to find Neu5Gc or reported it to be present only at very low levels (10,26,(81)(82)(83)(84)(85)(86)(87)(88). To confirm and extend these findings, we collected samples of brain tissue from chimpanzee, mouse, rat, cow, pig, and dolphin.…”
Section: Resultsmentioning
confidence: 81%
“…Relative Absence of Neu5Gc Is a Conserved Feature of Vertebrate Brain-Prior studies of sialic acids in the vertebrate brain have either failed to find Neu5Gc or reported it to be present only at very low levels (10,26,(81)(82)(83)(84)(85)(86)(87)(88). To confirm and extend these findings, we collected samples of brain tissue from chimpanzee, mouse, rat, cow, pig, and dolphin.…”
Section: Resultsmentioning
confidence: 81%
“…It remains to be seen whether the mutation in CMP-sialic acid hydroxylase can explain some of the dramatic morphological and functional changes that occurred during the evolution of humans. In this regard, perhaps the most intriguing observation is that no matter what the level of Neu5Gc was in other parts of the body, the amounts in the brain were always very low in a variety of animals studied (34)(35)(36), including the chimpanzee (37). This correlates with very low levels of hydroxylase message in the mouse brain (45).…”
Section: Discussionmentioning
confidence: 99%
“…The conversion from Neu5Ac to Neu5Gc can positively or negatively affect interactions involving several of the known endogenous and exogenous receptors for sialic acids such as CD22, myelin-associated glycoprotein, sialoadhesin, and the influenza A virus hemagglutinin (27)(28)(29)(30)(31)(32)(33). Interestingly, even in animals with large amounts of Neu5Gc in other tissues, its level in the brain is always extremely low (34)(35)(36). We recently reported a major biochemical difference between the great apes and humans, with the latter showing a loss of activity of the enzyme CMP-N-acetylneuraminic acid hydroxylase (37).…”
mentioning
confidence: 99%
“…Expression of Neu5Gc in the mammalian brain is very low, even in species like the mouse and chimpanzee, in which expression in other tissues can be high (26,29,37). Here we show that this is true even in the fetal state (note the negative staining of the brain in the WT fetal sections in Fig.…”
Section: Vol 27 2007 N-glycolylneuraminic Acid Deficiency In Mice 4343mentioning
confidence: 99%